2002
DOI: 10.1007/bf02988643
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine A2A receptor imaging with [11C]KF18446 PET in the rat brain after quinolinic acid lesion: Comparison with the dopamine receptor imaging

Abstract: We proposed [11C]KF18446 as a selective radioligand for mapping the adenosine A2A receptors being highly enriched in the striatum by positron emission tomography (PET). In the present study, we investigated whether [11C]KF18446 PET can detect the change in the striatal adenosine A2A receptors in the rat after unilateral injection of an excitotoxin quinolinic acid into the striatum, a Huntington's disease model, to demonstrate the usefulness of [11C]KF18446. The extent of the striatal lesion was identified base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 44 publications
3
24
0
Order By: Relevance
“…Most significant losses were detected in the dopaminergic (D 1 and D 2 receptors) and adenosinergic (A 2A receptor) receptor systems. These findings are in good accordance with human post-mortem studies (Glass et al 2000) that have been confirmed by in vivo PET studies, which clearly demonstrate a massive loss of D 2 dopamine (Turjanski et al 1995;Ginovart et al 1997;Antonini et al 1998;Araujo et al 2000;Pavese et al 2003) and A 2A adenosine (Ishiwata et al 2002) receptors, respectively. A reduction of NMDA receptor density, which has been described in the putamen of HD patients (Young et al 1988), could not be confirmed.…”
Section: Regional Pattern Of Receptor Changessupporting
confidence: 89%
“…Most significant losses were detected in the dopaminergic (D 1 and D 2 receptors) and adenosinergic (A 2A receptor) receptor systems. These findings are in good accordance with human post-mortem studies (Glass et al 2000) that have been confirmed by in vivo PET studies, which clearly demonstrate a massive loss of D 2 dopamine (Turjanski et al 1995;Ginovart et al 1997;Antonini et al 1998;Araujo et al 2000;Pavese et al 2003) and A 2A adenosine (Ishiwata et al 2002) receptors, respectively. A reduction of NMDA receptor density, which has been described in the putamen of HD patients (Young et al 1988), could not be confirmed.…”
Section: Regional Pattern Of Receptor Changessupporting
confidence: 89%
“…In patients and animals with HD, metabolic abnormalities and reductions in dopamine binding are well described in striatal and extrastriatal regions, progressively decreasing upon symptom severity [18,19,[41][42][43][44][45]. Here, [ 18 F]FDG values of the caudate-putamen were higher than, but positively correlated to D 2 impairment.…”
Section: Discussionmentioning
confidence: 84%
“…It is also possible that the expression of A 2A Rs might also increase in animal models and patients with Huntington's disease, since the expression of A 2A Rs is increased in neurons over-expressing huntingtin [213]. However, the major loss of medium spiny neurons in this condition may mask the increased density of A 2A Rs in the remaining viable neurons [211,214,215]. Interestingly, this idea that brain A 2A Rs might be up-regulated by noxious stimuli was most evident in a recent study focusing on extra-striatal regions.…”
Section: Modification Of Adenosine Metabolism On Stressful Conditionsmentioning
confidence: 99%